(3GdYbjOI GdeajOIs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN CHh GdaVd CMeO bGd obQjA Ydi CHj LYaQ eMeO Hf LQjQ GdWHQi hCf CSeY GdMeO ddg eadL GdMb hfGUQg heOMV GdHGWd heG Mbg GdPi ENJGQ dfaSg GdESdGe OjfkG aCeQ Hg hMGWg aJhcd HMaXg s
(3BNQgG (B:s
(3hdG JJHYhG YhQGJge aEfg ef JJHY YhQGJge JJHY Gddg YhQJg hef JJHY Gddg YhQJg jaVMg ai HjJg Je GdLRA HMeO Gddg hYhfg hUdi Gddg Ydi fHjfG eMeO hYdi Bdg hUMHg hSde JSdjekG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B147s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds